CYCLIC PEPTIDE AND PREPARATION METHOD THEREFOR, AND COMPLEX COMPRISING SAME AND USE THEREOF - ZENG, Dexing; LI, Wenjie; CHEN, Yinfei; SHAN, Changyu (2025)
Provided is a cyclic peptide, having a sequence of cyclo(X1X2X3X4X5X6), wherein X1 is asparagine; X2 is glycine or sarcosine; X3 is arginine; X4 is selected from a group consisting of threonine, tyrosine, and phenylalanine; X5 is lysine; and X6 is selected from a group consisting of tyrosine, valine, and glutamic acid. Provided is a method for preparing the cyclic peptide. Provided is a complex, comprising the cyclic peptide, a linker, and a chelating agent. Provided is a use of the complex as a radionuclide-labeled targeting molecule. Provided is a radionuclide labeling method, comprising contacting a complex that chelates a radionuclide with an object to be labeled by the radionuclide.